2013
DOI: 10.1152/ajprenal.00043.2013
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-metabolic derangement preserves hemodynamics but promotes intrarenal adiposity and macrophage infiltration in swine renovascular disease

Abstract: Obesity-metabolic disorders (ObM) often accompany renal artery stenosis (RAS). We hypothesized that the coexistence of ObM and RAS magnifies inflammation and microvascular remodeling in the stenotic kidney (STK) and aggravates renal scarring. Twenty-eight obesity-prone Ossabaw pigs were studied after 16 wk of a high-fat/high-fructose diet or standard chow including ObM-sham, ObM-RAS, Lean-RAS, or Lean-sham (normal control) groups. Single-kidney renal blood flow (RBF) and glomerular filtration rate (GFR) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 43 publications
(55 citation statements)
references
References 39 publications
0
55
0
Order By: Relevance
“…Hyperleptinaemia is positively correlated with the degree of obesity (Ahima & Flier 2000, Tam et al 2012 and is also associated with increased TGFB1 production and collagen deposition leading to increased fibrosis in CKD (Wolf & Ziyadeh 1999, Briffa et al 2013. Previous studies have established that fibrotic markers including TGFB1, collagen IV and VEGFA are up-regulated in the kidney in obesity-related nephropathy (Jiang et al 2005, Cignarelli & Lamacchia 2007, Mathew et al 2011, Briffa et al 2013, Nolan et al 2013, Zhang et al 2013. Indeed, it has been shown that in lean transgenic mice that overexpress CB 1 , there is an increase in glomerular expression of VEGFA (Hsu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperleptinaemia is positively correlated with the degree of obesity (Ahima & Flier 2000, Tam et al 2012 and is also associated with increased TGFB1 production and collagen deposition leading to increased fibrosis in CKD (Wolf & Ziyadeh 1999, Briffa et al 2013. Previous studies have established that fibrotic markers including TGFB1, collagen IV and VEGFA are up-regulated in the kidney in obesity-related nephropathy (Jiang et al 2005, Cignarelli & Lamacchia 2007, Mathew et al 2011, Briffa et al 2013, Nolan et al 2013, Zhang et al 2013. Indeed, it has been shown that in lean transgenic mice that overexpress CB 1 , there is an increase in glomerular expression of VEGFA (Hsu et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is also a key driver of diabetic nephropathy, and inflammation in adjacent perirenal adipose tissue exacerbates diabetic nephropathy (45). Adipose tissue shows increased adipocyte size, macrophage infiltration, and fibrosis in the setting of metabolic derangements (46,49). The perirenal adipose tissue from db/db mice showed a marked increase in inflammatory cells, concomitant with the increased adipocyte cross-sectional area and enhanced fibrosis in perirenal adipose tissue (Fig.…”
Section: Ang 1-7 Counteracts Ros Production and Reduces Inflammation mentioning
confidence: 99%
“…Fat measurement. Intra-abdominal adipose tissue was expressed as volume and fraction (21,22,39). With the use of Analyze, the attenuation range of subcutaneous fat tissue was used to automatically threshold the adipose tissue through the entire image.…”
Section: In Vivo Imaging Studiesmentioning
confidence: 99%